A privacy preserving authentication scheme for roaming services in global mobility networks. Issue 16 (9th February 2015) - Zhang, Gefei; Fan, Dan; Zhang, Yuqing; Li, Xiaowei; Liu, Xuefeng
Abstract To provide secure roaming services for mobile users in Global Mobility Networks, many schemes have been proposed in recent years. However, most of them focus only on authentication and fail to satisfy many practical security requirements such as user anonymity and untraceability. To address this problem, we propose a privacy‐preserving authentication scheme based on elliptic curve cryptography. The proposed scheme is provably secure under a formal model that satisfies all practical security requirements. Compared with existing authentication schemes, ours enjoys better performance in terms of computation cost and security. Copyright © 2015 John Wiley & Sons, Ltd.